2018
DOI: 10.5812/jjm.58591
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ubiquitin Like Protein-Proteasome System on the Drug Resistance of Isoniazid Mono-Resistant Mycobacterium tuberculosis

Abstract: Background: Tuberculosis (TB) is one of the most widespread and lethal infectious diseases worldwide. The emergence of drugresistant TB has hampered effective TB treatment and control. Prokaryotic ubiquitin-like Protein-Proteasome System (PPS) contributes to the survival of Mycobacterium tuberculosis in the host. However, whether PPS effects drug resistance of isoniazid monoresistant Mycobacterium tuberculosis (INH-MTB) is still unknown. Objectives: This study aimed at exploring the effect of PPS on drug resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…However, our data suggest that exposure of mouse peritoneal macrophages to C. septicum PPF≥100 kDa can trigger a cell response, including induction of TNFα and IL-10 expression (D.-L. Zhang et al 2017). Analysis of TNF-α and IL-10 was performed as part of a larger analysis of cytokines secreted by macrophages in response to the toxins contained in the PPF≥100 kDa.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, our data suggest that exposure of mouse peritoneal macrophages to C. septicum PPF≥100 kDa can trigger a cell response, including induction of TNFα and IL-10 expression (D.-L. Zhang et al 2017). Analysis of TNF-α and IL-10 was performed as part of a larger analysis of cytokines secreted by macrophages in response to the toxins contained in the PPF≥100 kDa.…”
Section: Discussionmentioning
confidence: 79%
“…It has been reported that these cytokines induce autophagy and apoptosis in macrophages (Djavaheri-Mergny et al 2006;Xu et al 2006); however, the mechanism remains to be fully understood. However, our data suggest that exposure of mouse peritoneal macrophages to C. septicum PPF≥100 kDa can trigger a cell response, including induction of TNFα and IL-10 expression (D.-L. Zhang et al 2017). Analysis of TNF-α and IL-10 was performed as part of a larger analysis of cytokines secreted by macrophages in response to the toxins contained in the PPF≥100 kDa.…”
Section: Septicum Ppf ≥100 Kda Affects Cytokine Expression In Mouse P...mentioning
confidence: 99%